2018
DOI: 10.1021/acs.jpcb.8b02292
|View full text |Cite
|
Sign up to set email alerts
|

Porphyrin–Coumarin Dyads: Investigation of Photophysical Properties and DNA Interactions

Abstract: Two new nonconjugated porphyrin-coumarin dyads with different orientations with respect to donor-acceptor entities and their zinc complexes were synthesized. Single-crystal structures of the free-base porphyrin-coumarin dyads were successfully resolved. The absorption spectra of the dyads were linear combinations of the spectra of their corresponding monomers, indicating a negligible electronic communication between the coumarin and porphyrin moieties. However, the fluorescence emission of the coumarin entity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…Alkylation of 6 with 7 was achieved in DMF at room temperature over 5 d with potassium carbonate as the base in a procedure adapted from Wang and Liu. 39 Complexation of 8 with FeCl 2 ·4H 2 O in chloroform/methanol (3:1) and methyl ester hydrolysis under basic conditions gave rise to the formation of complex Fe–L 1 . Ester hydrolysis after metal complexation was found to be much more effective.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Alkylation of 6 with 7 was achieved in DMF at room temperature over 5 d with potassium carbonate as the base in a procedure adapted from Wang and Liu. 39 Complexation of 8 with FeCl 2 ·4H 2 O in chloroform/methanol (3:1) and methyl ester hydrolysis under basic conditions gave rise to the formation of complex Fe–L 1 . Ester hydrolysis after metal complexation was found to be much more effective.…”
Section: Resultsmentioning
confidence: 99%
“…Such a high efficiency supports the literature precedent of an efficient intramolecular energy transfer between coumarin donor and porphyrin acceptor fluorophores. 38 , 39 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The corresponding free-base porphyrins analogues were successfully obtained in the presence of concentrated hydrochloric acid in chloroform at room temperature in good yields, Scheme 76. [103] Lately, Tekuri and co-workers [104] described the synthesis of nickel, copper and zinc complexes of coumarin-fused pyrido [2,3-b]porphyrins via one-pot reaction from 2-amino-mesotetraphenylporphyrin, aromatic aldehydes and 4-hydroxycoumarin., Scheme 77. The preliminary photophysical study of meso-tetraphenyl-porphyrin precursors showed a significant redshift in their electronic absorption and emission spectra.…”
Section: Synthesis Of Coumarin-porphyrin Macrocyclesmentioning
confidence: 99%